European Union member states preparing for Europe 2020. An application of the MULTIMOORA method - Brauers, Willem Karel M.; Baležentis, Alvydas; Baležentis, Tomas (Technological and Economic Development of Economy, 2012)
It is the intention of the European Union to create a growing and sustainable European economy by 2020, a much more moderate target than the 2010 target of becoming the most competitive and dynamic knowledge-based economy in the world. This intention has to be supported by an adequate Optimization and Decision Support System.Therefore, MULTIMOORA is proposed. MULTIMOORA is a quantitative method, which compares multiple and optimum objectives, expressed in different units, as much as possible on a non-subjective basis. In opposition to similar methods MULTIMOORA does not need normalization, being based on dimensionless measures. Importance of an objective can eventually be given by the stakeholders concerned. MULTIMOORA is composed of three approaches: Ratio System, Reference Point and Multiplicative Form Methods, all of the same importance and each controlling each other. Twenty two objectives, 10 originating from statistics and 12 from statistics and forecasts, important for the future, characterize the 27 EU-Countries economies as a preparation for 2020. Which of these countries are the best prepared for 2020? A Dominance Theory, summarizing the three obtained ordinal numbers per country, ranks the 27 countries for that purpose.